Phenolic Diterpenes from Rosemary Suppress cAMP Responsiveness of Gluconeogenic Gene Promoters. (23rd August 2012) - Yun, Young Sook; Noda, Sachie; Shigemori, Genta; Kuriyama, Ryunosuke; Takahashi, Shigeru; Umemura, Mariko; Takahashi, Yuji; Inoue, Hideshi
<x xml:space="preserve">Abstract</x> The cAMP/protein kinase A/cAMP response element (CRE)‐binding protein pathway is important for various physiological aspects including regulation of gluconeogenic gene expression. Rosemary, a well‐known herb, has been reported to decrease blood glucose levels. We found that methanol extracts of rosemary suppressed forskolin (FSK)‐stimulated luciferase expression under the control of CRE, as well as the promoters for cytosolic phosphoenolpyruvate carboxykinase (PEPCK‐C) and glucose‐6‐phosphatase (G6Pase) catalytic subunit genes in human hepatoma HepG2 cells. Three abietane‐type diterpenes and two flavonoids were isolated from the rosemary extracts. Among these, 7‐O‐methylrosmanol (1) and royleanonic acid (3) effectively suppressed FSK‐induced luciferase expression under the control of the CRE, PEPCK‐C and G6Pase gene promoters. PEPCK‐C and G6Pase, which play a key role in the homeostatic regulation of blood glucose levels, are important for managing type II diabetes mellitus. Therefore, the ability of rosemary and its components to suppress cAMP responsiveness of the PEPCK‐C or G6Pase gene may contribute to its antihyperglycemic activity. Copyright © 2012 John Wiley & Sons, Ltd.